Diftong dan Kluster Penelitian pada Masyarakat Bakongan, Kabupaten Aceh Selatan - Syamsiah, Syamsiah; Qistina, Nurul Ain; Alfiaturrahmi, Alfiaturrahmi; Izzati, Rahmi; Lestari, Sarima (Multiverse: Open Multidisciplinary Journal, 2024)
This study investigates the phonological features of the Acehnese language, focusing on the dialect spoken in Bakongan, South Aceh. The research aims to explore the use of diphthongs and consonant clusters as distinctive elements that reflect regional variation within the Acehnese linguistic landscape. Employing a qualitative descriptive method, this study analyzes data derived from native speaker utterances, emphasizing phonetic patterns and phonological shifts. The findings reveal several unique diphthong forms in the Bakongan dialect, including /eu/, /ie/, /ée/, /eue/, /oe/, /ue/, /ai/, and /oi/, which differ in both usage and distribution from those in standard Acehnese. Furthermore, the study highlights the prominence of consonant clusters—particularly those involving the consonant "r"—as a marked feature in the speech of Bakongan speakers. These phonological variations contribute to the dialect's distinctiveness and underline the internal diversity of the Acehnese language. In conclusion, the research underscores the necessity of documenting local dialects to preserve linguistic richness and to support broader efforts in language maintenance and revitalization, especially in multilingual regions like Aceh.